Upper limb prosthesis users: A longitudinal cohort study. Issue 5 (31st October 2021) - Resnik, Linda; Borgia, Matthew; Cancio, Jill; Heckman, Jeffrey; Highsmith, Jason; Levy, Charles; Webster, Joseph
Abstract : Background: No previous studies have followed prosthesis users with upper limb loss or limb deficiency using their own prostheses to assess change over time. Objectives: (1) To describe prostheses and terminal device types used at baseline and 1-year follow-up; (2) to examine changes in functional outcomes and device satisfaction over time; and (3) to examine whether changes in outcomes varied across level of amputation and type of prosthesis used. Study Design: Multisite, observational time series design with in-person functional performance and self-report data collected at baseline and 1-year follow-up. Methods: Baseline and follow-up outcome scores were compared using Wilcoxon signed-rank tests. Analyses were stratified by amputation level, time since amputation, prosthesis type, and change in device type. Published minimal detectable change (MDC) values were used to determine whether detectable change in outcome measures occurred. Results: The longitudinal cohort consisted of 64 participants (mean age 64 years, 56% body-powered users). The only significant differences in outcome measures between baseline and follow-up (after adjustment for false discovery) were hours/day of prosthesis use, which increased from 6.0 (4.4) to 7.3 (5.3) hours ( P = 0.0022). Differences in prosthesis use intensity remained significant in analyses stratified by amputation level, time since amputation, prosthesis type, and change in device type. Between 14 and 20% of the sample had change in one or more outcome measures that was greater than the known MDC. Conclusions: Most participants had stable outcomes over a year's time, whereas 14–20% experienced either improvement or decline in one or more tests indicating the importance of annual follow-up visits.